Oxidative stress in prefrontal cortex of rat exposed to MK-801 and protective effects of CAPE - Ozyurt, Birsen; Ozyurt, Huseyin; Akpolat, Nusret; Erdogan, Hasan; Sarsilmaz, Mustafa (Pergamon-Elsevier Science Ltd, 2007)
MK-801 was shown to be one of the most neurotoxic non-competitive NMDA receptor antagonists. It is known that repeated injection of MK-801 was proposed in an animal model in psychosis. The aims of this study are to investigate the contributing effect of oxidative stress in MK-801-induced experimental psychosis model, and to show that prevention of oxidative stress may improve prognosis. Furthermore, there is evidence that oxygen free radicals play an important role in the pathophysiology of schizophrenia. In this study, Wistar Albino rats were divided into three groups: 1st group: Control, 2nd group: MK-801, 3rd group: MK-801 + CAPE (Caffeic acid phenethyl ester) group. MK-801 was given intraperitoneally at the dose of 0.5 mg/kg/day for 5 days. CAPE was given to the treatment group while exposed to MK-801. In control group, saline was given intraperitoneally at the same time. After 7 days, rats were killed by decapitation. Prefrontal cortex (PFC) of rats was removed for biochemical and histological analyses. As a result, malondialdehyde (MDA), protein carbonyl (PC), nitric oxide (NO) levels and superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and xanthine oxidase (XO) and adenosine deaminase (AD) enzyme activities were found to be increased significantly in prefrontal cortex (PFC) of MK-801 group (p < 0.0001) compared to control group. In CAPE treated rats, prefrontal tissue MDA, PC, NO levels and, GSH-Px, XO, AD enzyme activities were significantly decreased when compared to MK-801 groups (p < 0.0001) whereas catalase (CAT) enzyme activity was not changed. Moreover, in the light of microscopic examination of MK-801 groups, a great number of apoptotic cells were observed. CAPE treatment decreased the apoptotic cell count in PFC. The results of this study showed that MK-801-induced neurotoxicity caused oxidative stress in PFC of rats. This experimental study may also provide some evidences for the new treatment strategies with antioxidants in schizophrenia. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: CAPE; MK-801; nitric oxide; oxidative stress; prefrontal cortex; schizophrenia